Gastrointestinal symptoms in long-distance runners, cyclists, and triathletes: prevalence, medication, and etiology - Peters, H. P.; Bos, M.; Seebregts, L.; Akkermans, L. M.; van Berge Henegouwen, G. P.; Bol, E.; Mosterd, W.; de Vries, W. R. (The American Journal of Gastroenterology, 1999)
OBJECTIVE: The aim of this study was to determine the prevalence of exercise-related gastrointestinal (GI) symptoms and the use of medication for these symptoms among long-distance runners, cyclists, and triathletes, and to determine the relationship of different variables to GI symptoms. METHODS: A mail questionnaire covering the preceding 12 months was sent to 606 well-trained endurance type athletes: 199 runners (114 men and 85 women), 197 cyclists (98 men and 99 women), and 210 triathletes (110 men and 100 women) and sent back by 93%, 88%, and 71% of these groups, respectively. Symptoms were evaluated with respect to the upper (nausea, vomiting, belching, heartburn, chest pain) or lower part of the GI tract (bloating, GI cramps, side ache, urge to defecate, defecation, diarrhea). For statistical analysis, Mann-Whitney U test, Fisher exact test, or Student t test were used. RESULTS: Runners experienced more lower (prevalence 71%) than upper (36%) GI symptoms during exercise. Cyclists experienced both upper (67%) and lower (64%) symptoms. Triathletes experienced during cycling both upper (52%) and lower (45%) symptoms, and during running more lower (79%) than upper (54%) symptoms. Bloating, diarrhea, and flatulence occurred more at rest than during exercise among all subjects. In general, exercise-related GI symptoms were significantly related to the occurrence of GI symptoms during nonexercise periods, age, gender, diet, and years of training. The prevalence of medication for exercise-related GI symptoms was 5%, 6%, and 3% for runners, cyclists, and triathletes, respectively. CONCLUSIONS: Long-distance running is mainly associated with lower GI symptoms, whereas cycling is associated with both upper and lower symptoms. Triathletes confirm this pattern during cycling and running. The prevalence of medication for exercise-related GI symptoms is lower in the Netherlands in comparison with other countries, in which a prevalence of 10-18% was reported. More research on the possible predisposition of athletes for GI symptoms during exercise is needed.